2015
DOI: 10.1080/09276440.2015.1053753
|View full text |Cite
|
Sign up to set email alerts
|

A comparative evaluation between flat and traditional energy directors for ultrasonic welding of CF/PPS thermoplastic composites

Abstract: Energy directors, responsible for local heat generation in ultrasonic welding, are neat resin protrusions traditionally moulded on the surfaces to be welded. This study evaluates an alternative energy directing solution for ultrasonic welding of thermoplastic composites based on the usage of a loose flat layer of neat resin at the welding interface, referred to as 'flat energy director'. Analysis of dissipated power, displacement of the sonotrode, welding energy and time as well as weld strength compared to mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(16 citation statements)
references
References 9 publications
0
16
0
Order By: Relevance
“…The design of ED plays a very important role to get a sound welding, since their shape, size, morphology and their configuration, influence the final weld quality. Different shapes of energy directors can be designed, such as semicircular, triangular, rectangular, multiple EDs and others [41,51,90]. They can also be oriented in the parallel or perpendicular direction of welded joints, and their effects could be compared.…”
Section: Energy Directormentioning
confidence: 99%
See 1 more Smart Citation
“…The design of ED plays a very important role to get a sound welding, since their shape, size, morphology and their configuration, influence the final weld quality. Different shapes of energy directors can be designed, such as semicircular, triangular, rectangular, multiple EDs and others [41,51,90]. They can also be oriented in the parallel or perpendicular direction of welded joints, and their effects could be compared.…”
Section: Energy Directormentioning
confidence: 99%
“…Villegas et al, in one the investigation, has shown that flat ED has no negative impact on the welding process or quality while comparing it with traditional ED (Triangular) [90]. Influence on LSS with and without ED was investigated by Tao et al, using CF/PEEK and ED of 0.45 mm thickness [51].…”
Section: Energy Directormentioning
confidence: 99%
“…Applications and research activities in ultrasonic welding of TPC have been deeply reviewed and conducted by Villegas et al [ 33 , 81 , 82 , 87 , 147 , 148 , 149 , 150 , 151 , 152 ]. The size, shape, and number of energy directors affect the heat generation and resin flow.…”
Section: Tpc Joining and Repair Techniquesmentioning
confidence: 99%
“…There are considerable research literatures on the USW process for thermoplastic materials at the coupon level [125][126][127][128][129][130][131][132][133][134][135]. The welded condition parameters including welding time, welding pressure, and vibration amplitude, were investigated and the relationship between the welded ability and the parameters were reported.…”
Section: New Ultrasonic Welding Application For Polymersmentioning
confidence: 99%